2021
DOI: 10.3390/ijms22020810
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Stimulation of Prelimbic Pyramidal Neurons Maintains Fear Memories and Modulates Amygdala Pyramidal Neuron Transcriptome

Abstract: Fear extinction requires coordinated neural activity within the amygdala and medial prefrontal cortex (mPFC). Any behavior has a transcriptomic signature that is modified by environmental experiences, and specific genes are involved in functional plasticity and synaptic wiring during fear extinction. Here, we investigated the effects of optogenetic manipulations of prelimbic (PrL) pyramidal neurons and amygdala gene expression to analyze the specific transcriptional pathways associated to adaptive and maladapt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…However, the elevation of spine size of IL neurons returned to the level observed in pseudo-conditioned mice [93]. In the PL, it is reported that apical dendrites of pyramidal neurons showed decreased spine density in animals underwent extinction training compared to no extinction group (Table 1) [94].…”
Section: Synaptic Plasticity Induced By Fear Extinctionmentioning
confidence: 75%
“…However, the elevation of spine size of IL neurons returned to the level observed in pseudo-conditioned mice [93]. In the PL, it is reported that apical dendrites of pyramidal neurons showed decreased spine density in animals underwent extinction training compared to no extinction group (Table 1) [94].…”
Section: Synaptic Plasticity Induced By Fear Extinctionmentioning
confidence: 75%
“…To confirm the specificity and expression pattern of β2-AR in mFPC, we used new β2-AR antibody from another company to co-stain with CaMKIIα and found a similar result ( Supplementary Figure S1a ). Then, to specifically manipulate mPFC β2-AR in real time, we utilized β2-AR optogenetics, which is similar in dynamics to endogenous β2-AR [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…To dissect the roles of mPFC β2-AR in anxiety-like behavior, we recruit optogenetics to specifically manipulate β2-AR activity [ 26 , 27 ] and miRNA based silencing to knock down β2-AR expression within the pyramidal neurons of the mPFC. Our data show that optogenetic activation of β2-AR is sufficient to induce anxiety-like behavior and β2-AR knock down can induce an anxiolytic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic observation methods mainly utilized devices, including MRI, PET, and SPECT (Conway et al, 2006;Malbert et al, 2019;Borgmann et al, 2021), whose major advantages lay in the power to observe the functional connectivity of multiple brain regions. The microscopic observation methods primarily utilized electrophysiology and optical fiber photometry, which took advantage of observing microstructures such as cells or neurons (Jaseja, 2010;Laricchiuta et al, 2021). However, few studies effectively combined the two observation technology to decipher complex brain neuronal activities in vivo.…”
Section: Experimental Observation Platform and Mouse Modelmentioning
confidence: 99%